asy-Syi’ru “Man ‘Allamani Hubban Kuntu lahu ‘Abdan” li Nizar Qabbani (at-Tahlil as- Simiyai li Michael Riffaterre) - Abdul Latif; Nur Safitri (Jurnal Internasional Pendidikan Bahasa Arab, 2019)
The poetry was "Who taught me love I used to be his slave" was born from the pen of the contemporary poet Nizar Qabbani. This poetry tells of a servant's optimism in a teacher’s search that he can teach many things. But his research into the teacher who taught him many things was still scattered in verses of poetry. The semiotic theory of Michael Riffaterre aims to find the unity of meaning in poetry. Therefore, the researcher used in this research the semiotic theory of Michael Riffaterre. The research results obtained by the researcher are the unity of meaning mentioned in the pattern of poetry, which is the optimism of the person in the teacher’s research and learning from him to obtain the knowledge he wants. The models in this poem are "Who taught me how to love a woman to the point of delirium." The actual hypogram that represents the background of this poetry is in the story of optimism of the Prophet Moses to learn from the Prophet of Khidr in Surat Al-Kahf. The potential hypogram in this poetry is optimism and love, because love, which can give us an optimistic way to search for something we want.